PENURUNAN KADAR SIANIDA LIMBAH CAIR INDUSTRI TAPIOKA DENGAN LARUTAN KAPUR TOHOR (Ca(OH)2) DI DESA NGEMPLAK KIDUL, MARGOYOSO, PATI - Sharadifa Putika Apsari; Onny Setiani; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Based on the preliminary studies, cyanide level of tapioca industry waste water in UD SM was 44,40 mg/l. This level exceeds standart quality of cyanide in tapioca industry waste water is 0,3 mg/l. Therefore, it was necessary to waste water treatment, one of them with coagulation-flocculation system using quicklime solution (Ca(OH2)). The purpose of this study was to determined the effect of the addition of quicklime soluiton (Ca(OH)2) on various doses to reduced cyanide level in tapioca industry waste water. The type of research was quasi experimental research with pretest-postest with control group design. The sample in this research was part of waste water from UD SM that taken directly through the waste water tank outlet pipe. Total sample for 4 treatment (2,5%; 5%; 7,5%; and 10%) with 6 replication was 36 samples. Data analysis used One Way Anova test showed that there was difference in cyanide (CN) levels of tapioca industry waste water in various groups variations in the concentration of quicklime solution (Ca(OH2)) with p-value = 0,000 (p≤0,05). The result of Post Hoc test, showed that groups between variations in dose that has a significant difference with cyanide level reduction is 7,5% dose which has a significant difference to all groups of dose treatment. The average cyanide level after treatment has decreased gradually as more doses of tohor lime solution (Ca(OH2)). The largest decrease occurred at a dose concentration of 7,5%, which decreased cyanide level to 16,32 mg/l with a percentage decrease was 66,88%. These results still exceed standard, so further research is needed to reduce cyanide level of tapioca waste water to below the quality standard.